Gambaran Kadar Glukosa Darah Sewaktu Pada Ibu Hamil di Puskesmas Tambelan Sampit Kota Pontianak - Ramadan, Aditiya; Nuswantoro, Ari; Triana, Linda; Ihsan, Bagus Muhammad (Jurnal Ners, 2024)
characterised by high blood sugar levels as well as problems with protein, lipid, and carbohydrate metabolism as a result of inadequate insulin activity. Patients who have wounds infected by pathogenic bacteria, both Gram positive and Gram negative, run the risk of developing a number of problems, including neuropathy, hypertension, coronary heart disease, retinopathy, nephropathy, and gangrene. This cross-sectional, observational, descriptive study aims to pinpoint pathogenic bacteria in the diabetic patients' wounds at the diabetes wound care clinic in Pontianak City. The bacterial identification stage includes inoculation on enrichment media, Gram staining, inoculation and observation of colonies on differential-selective media, and biochemical tests. Examination results showed that Klebsiella pneumoniae was identified in 20 samples (57%), Pseudomonas aeruginosa in 8 samples (23%), and Staphylococcus aureus in 7 samples (20%). According to the study, diabetic wound problems put DM patients at risk of contracting dangerous microorganisms and spreading them to others. In order to prevent infection and other health issues, patients are instructed on how to properly care for their wounds. They are also provided the correct follow-up by medical professionals.